Sociocultural and Pragmatic Preconditions For The Use of Foreign Insertions - Bozorova Umida; Isakova Nodira Azzamovna (Academicia Globe: Inderscience Research, 2026)
This article examines the sociocultural and pragmatic preconditions for the use of foreign-language insertions in the prose of Alexander Pushkin within the historical and literary context of the first third of the nineteenth century. French and German, functioning as symbols of cultural capital and markers of aristocratic identity, played a crucial role in shaping salon, academic, military, and professional discourse in Russian high society. The study analyzes the multifunctional nature of interlingual insertions in Pushkin’s works, particularly in The Captain’s Daughter and The Queen of Spades, demonstrating that such elements serve not merely as stylistic embellishments but as complex semiotic devices. The research concludes that foreign-language fragments in Pushkin’s prose form a multilayered continuum in which sociocultural symbolism, pragmatic function, and compositional strategy intersect. Understanding these interrelations is essential for structural-semantic analysis and for developing effective translation approaches that preserve the semantic, pragmatic, and stylistic integrity of the original text